Does father's class or mother's education matter more? Decomposing and contextualising the influence of social origin on adult learning participation. Issue 2 (4th March 2023) - Haralampiev, Kaloyan; Ilieva-Trichkova, Petya; Boyadjieva, Pepka
ABSTRACT: This article argues for the need to regard social origin as a complex phenomenon in order to better understand the determinants of individuals' participation in adult learning. It: 1) discusses the conceptualisation of social origin; 2) analyses how two of its components – parental (both father's and mother's) class and education – are interrelated with participation in non-formal job-related adult learning; 3) explores whether this relationship is embedded in different welfare regimes. We argue that social origin includes different interrelated but not interchangeable components that refer to both fathers and mothers. Each one of them has its own influence and that is why all of them should be considered at once in exploring adults' involvement in learning. Empirically, the analyses are based on the latest data from the ninth round of the European Social Survey, carried out in 2018, for 29 countries. The data were analysed with logistic regression modelling. The results show that parental (mother's and father's) class and education have an independent influence on individuals' participation in adult learning and that this influence is embedded in different welfare regimes creating considerable differences between welfare regimes in terms of whether father's or mother's characteristics and which ones are more important.